Trabalho escravo contemporâneo : alguns aspectos subjetivos na relação de escravidão - Britto, Danielle Cristina Pereira (2020)
Contemporary slave labor is a social problem that has several facets. Its consolidation in Brazil is the result of an intense social inequality, which increasingly divides the country into rich and poor, favoring the abyss between the two classes. The relationship of neoliberal progress, capitalism, corruption and social inequality shows us that situations of extreme human exploitation, such as slave labor, have a certain permissiveness to be neglected and / or trivialized. It is in view of this panorama that this dissertation consists of a proposal for an exploratory-qualitative study, which aimed to raise the following question: what are the subjective aspects manifested in slavery relations? This questioning was achieved through semi-structured and open interviews, and participant observation, in which we can observe graduates of contemporary slave labor in Brazil. The analysis was carried out according to the content analysis of Laurence Bardin, from which the main elements contained in the narratives are grouped. We can thus see that among the main subjective manifestations present in the relationship between the graduates of contemporary slave labor and their experiences of slavery are the denials of self-recognition as slaves, the parental helplessness suffered and the violence (physical and psychological) resulting from slavery and the difficulties in elaborating them.